THE DIFFERENCES OF LEARNING OUTCOMES BETWEEN STUDENT WHO ARE TAUGHT BY NUMBER HEAD TOGETHER (NHT) AND JIGSAW COOPERATIVE TECHNIQUE LEARNING METHOD IN CLASS VII JUNIOR HIGHT SCHOOL 1 GANGGA - didi kuswara (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2018)
This study aims to determine the differences in learning outcomes between students who are taught by using cooperative learning NHT technique with Jigsaw technique in class VII SMPN 1 Gangga in the academic year 2011/2012. The research is a quasi-experimental design so that the populations in this study were all students of class VII and the sample of this research is class VII E and VII F taken using purposive sampling technique in which the class VII E amounted to 31 people as the control class with NHT technique and class VII F amounted to 32 people as a class experiment treated Jigsaw technique. The research instrument used a test result in the form of pretest and posttest learning and learning enforceability observation sheet. Based on the analysis of data obtained by the average value of 75.15 experimental class with the highest score of 100 and the lowest value of 50 and a student who reached KKM ≥ 65 as many as 25 students and 7 students who fail, while the control class average value of 71, 45 with a highest score of 100 and the lowest value of 45 and a student who reached KKM ≥ 65 were 22 students and 9 students who fail. Based on the analysis of hypothesis test acquired t test at 2,69 whereas t table at 2,00. Because of t test > t table, it can be concluded that there are differences in learning outcomes between students who are taught by using cooperative learning NHT technique with Jigsaw technique. In which the learning outcomes of students with Jigsaw technique is greater than the NHT technique.